2022
DOI: 10.34246/ahbvuhfd.1172511
|View full text |Cite
|
Sign up to set email alerts
|

Okullarda Akran Zorbaliğinin Özel Hukuk Açisindan Değerlendi̇ri̇lmesi̇

Abstract: Yabancı psikoloji doktrininden kaynağını alan akran zorbalığı (peer bullying) terimi, yerli doktrinde de benimsenmiştir. Son zamanlarda ise, bu ifadeye sadece doktrinde değil; eğitim dünyasında, medyada ve hatta ilk ve orta dereceli okullarda bir çocuğun velisi olan ana babalar arasındaki günlük konuşmalarda dahi rastlanabilmektedir. Doktrinde geleneksel zorbalık ve siber zorbalık şeklinde sınıflandırılan akran zorbalığı, Dünya Sağlık Örgütü tarafından bir halk sağlığı sorunu olarak kabul edilmektedir. Çocukla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…When they look at the outside world from their own small window, children who see violence as a problem-solving method, unfortunately, do not hesitate to use this method in their social relations. In recent studies, it has been reported that aggressive behaviors, which are described as "peer bullying", are frequently encountered among children all over the world (Kılınç, 2022). than social cohesion.…”
Section: Introductionmentioning
confidence: 99%
“…When they look at the outside world from their own small window, children who see violence as a problem-solving method, unfortunately, do not hesitate to use this method in their social relations. In recent studies, it has been reported that aggressive behaviors, which are described as "peer bullying", are frequently encountered among children all over the world (Kılınç, 2022). than social cohesion.…”
Section: Introductionmentioning
confidence: 99%